2015
DOI: 10.1262/jrd.2014-051
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of uterine bacterial infection, and its associations with endometritis and ovarian function in postpartum dairy cows

Abstract: We investigated the relationship between the persistence of uterine bacterial infections with cytologically determined endometritis and ovarian function in 65 postpartum Holstein cows. Vaginal mucus discharges were collected, and endometrial smear samples (n = 130) were collected for cytological and bacteriological examinations from the cows at weeks 5 and 7 postpartum (pp). Blood samples were collected at weeks 3, 5 and 7 pp to determine plasma progesterone concentrations to monitor ovarian activity. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 49 publications
2
29
2
1
Order By: Relevance
“…Eleven out of 17 (64Á7%) uterine samples had polymorphonuclear neutrophils (PMNs), more than 3% of which confirmed the presence of endometritis in these cows. A low (Bara nski et al 2012) to moderate (Ghanem et al 2015) correlation between the uterine cytology and bacteriology has been previously reported in postpartum endometritic dairy cows. Out of seven isolates of Staphylococcus aureus from the uterine samples, 6 (85%) were coagulase positive.…”
Section: Resultsmentioning
confidence: 91%
“…Eleven out of 17 (64Á7%) uterine samples had polymorphonuclear neutrophils (PMNs), more than 3% of which confirmed the presence of endometritis in these cows. A low (Bara nski et al 2012) to moderate (Ghanem et al 2015) correlation between the uterine cytology and bacteriology has been previously reported in postpartum endometritic dairy cows. Out of seven isolates of Staphylococcus aureus from the uterine samples, 6 (85%) were coagulase positive.…”
Section: Resultsmentioning
confidence: 91%
“…Some biological markers such as CD4 +, CD14 + and CD25 + leukocyte cells were in lesser concentrations in cows with SCE in peripheral blood. CD21 + and CD8 + lymphocyte cells were significantly decreased in SCE cows from uterine flushes (Ghanem et al, 2015).…”
Section: Immune Responsementioning
confidence: 88%
“…The process through which bacteria exerts its effects is still uncertain. It is clear that the presence of bacteria is related to clinical and/or subclinical uterine inflammation (Ghanem et al, 2015). The presence of specific bacterial populations in the uterus is also a factor involved in uterine disease.…”
Section: Infectious Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Ghanem et al [23] reported that while some cows presented with cytological endometritis without clinical endometritis, some others presented with clinical endometritis without cytological endometritis. The assumption that purulent vaginal discharge is associated with endometrial inflammation has never been validated [20].…”
Section: Discussionmentioning
confidence: 99%